2012
DOI: 10.3390/molecules170911269
|View full text |Cite
|
Sign up to set email alerts
|

Association of KIF6 Variant with Lipid Level and Angiographic Coronary Artery Disease Events Risk in the Han Chinese Population

Abstract: KIF6 is a class of molecular motor from the kinesin superfamily. Recently, multiple large studies consisting mainly of Europeans have shown that KIF6 Trp719Arg SNP may be a new predictive factor for coronary artery disease (CAD) event risk. The allelic frequency distribution of rs20455 is different in various populations, yet studies among the Han population, one of the largest ethnic groups in the World, have not been conducted. This study is aimed to evaluate the association of KIF6 Trp719Arg variant with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 30 publications
2
20
0
1
Order By: Relevance
“…Collectively, genome-wide association studies have identified SNPs in at least 95 loci, the combined effects of which account for approximately 10–12% of the total variance in HDL and TG levels [ 35 ]. Previously, we verified that the common KIF6 polymorphism Trp719Arg is involved in lipid metabolism and CHD, reporting that it was associated with significantly higher TG levels with increased myocardial infarction risk in angiographic CHD patients [ 24 ]. The characteristic features of diabetic dyslipidemia are increased concentrations of plasma TG and small dense LDL-C particles and decreased HDL-C [ 36 ].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Collectively, genome-wide association studies have identified SNPs in at least 95 loci, the combined effects of which account for approximately 10–12% of the total variance in HDL and TG levels [ 35 ]. Previously, we verified that the common KIF6 polymorphism Trp719Arg is involved in lipid metabolism and CHD, reporting that it was associated with significantly higher TG levels with increased myocardial infarction risk in angiographic CHD patients [ 24 ]. The characteristic features of diabetic dyslipidemia are increased concentrations of plasma TG and small dense LDL-C particles and decreased HDL-C [ 36 ].…”
Section: Discussionmentioning
confidence: 94%
“…The KIF6 gene spans a genomic region of about 390,000 base pairs on human chromosome 6p21, containing 23 exons and 22 introns [ 13 ]. Since 2007, there have been multiple large prospective and case-control studies on the association of a common KIF6 gene polymorphism—Trp719Arg single-nucleotide polymorphism (SNP) (rs20455)—with CHD risk [ 14 23 ], and a significant relationship between the KIF6 Trp719Arg polymorphism and CHD has been observed in several ethnic groups [ 15 , 18 , 21 , 22 , 24 26 ]. Accumulating evidence has suggested that KIF6 rs20455 may be a new predictive factor for risk of CHD occurrence and a genetic determinant of the plasma lipid level [ 24 , 25 , 27 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are several explanations for the present outcomes concerning the lack of association of Trp719Arg with CHD. First, there are differences in diagnosis in the population of patients and, second, the discrepancy of association between populations may be attributed to different genetic backgrounds and environmental factors [13, 16]. …”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis of the KIF6 Trp719Arg genotype from non-European populations ( Bare et al, 2010 , Bhanushali et al, 2011 , Peng et al, 2012 , Wu et al, 2012 ) was performed along with the data of the present study in both dominant and allelic models using fixed and random effects ( Helfenstein, 2002 ). The meta-analysis was carried out by comprehensive meta-analysis software [Biostat, USA].…”
Section: Methodsmentioning
confidence: 99%